High-strength steel sheet and method for producing same, and member and method for producing same
By controlling the composition and microstructure of high-strength steel plates, the problem of lower fracture resistance after forming in the prior art is solved, and the high yield strength, excellent collision endurance and fracture resistance of the steel plate are achieved, which is suitable for lightweight design of automotive parts.
Patent Information
- Application Number
- CN202380060093.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-29
- Filing Date
- 2023-07-25
- Publication Date
- 2025-03-14
AI Technical Summary
After forming and processing, the existing high-strength steel plate with a yield strength of 800 MPa or above, the residual austenite phase changes into hard martensite, resulting in a decrease in collision fracture resistance and making it difficult to meet the requirements of automobile components for collision endurance.
By controlling the composition and microstructure of the steel plate, the diffusible hydrogen in the steel is ensured to be less than 0.50 mass ppm, the total area ratio of tempered martensite and bainite is between 55 and 95%, the average particle size of residual austenite is less than 5.0 μm, and specific heating and cooling control are carried out during the heat treatment process to form excellent structure S1 and S2 ratios.
It realizes the yield strength of the steel plate above 800MPa, excellent collision endurance and fracture resistance, and is suitable for the lightweight design of automotive parts.
Smart Images

Figure CN119630828A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a high-strength steel plate having a yield strength (YS) of 800 MPa or more, a method for producing the same, and a component and a method for producing the same. Background Art
[0002] In recent years, for example, in the automotive industry, in order to protect the global environment, in order to reduce carbon dioxide (CO 2 ) emissions, hoping to improve the fuel efficiency of the car.
[0003] In order to improve the fuel efficiency of automobiles, it is effective to seek to reduce the weight of the vehicle body, but in this case, it is necessary to seek to reduce the weight of the vehicle body while maintaining the strength of the vehicle body. If the steel plates that become automobile parts can be made stronger and the structure of the vehicle body can be simplified to reduce the number of parts, the weight of the vehicle body can be reduced.
[0004] For example, Patent Documents 1 to 3 disclose high-strength steel sheets having a yield strength of 800 MPa or more.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2018-21231
[0008] Patent Document 2: Japanese Patent No. 2018-21233
[0009] Patent Document 3: Japanese Patent No. 2017-214647 Summary of the invention
[0010] Problems to be solved by the invention
[0011] High-strength steel sheets having a yield strength of 800 MPa or more generally improve workability through the TRIP (Transformation Induced Plasticity) effect of retained austenite.
[0012] That is, the retained austenite is transformed into martensite by the TRIP effect during processing, thereby improving the strength, and improving the ductility by improving the strain dispersion capability.
[0013] However, when such a steel sheet is formed into an automobile part, retained austenite may transform into hard martensite, which may reduce the fracture resistance during collision (hereinafter also simply referred to as "fracture resistance").
[0014] Furthermore, steel sheets used as automobile parts are also required to have excellent resistance during collision (hereinafter referred to as "collision resistance").
[0015] Therefore, an object of the present invention is to provide a high-strength steel sheet having a yield strength of 800 MPa or more and excellent in collision resistance and fracture resistance.
[0016] Methods used to solve problems
[0017] The present inventors have found that the above-mentioned object can be achieved by adopting the following configuration, thereby completing the present invention.
[0018] That is, the present invention provides the following [1] to
[10] .
[0019] [1] A high-strength steel sheet comprising a steel sheet, wherein the amount of diffusible hydrogen in the steel of the steel sheet is 0.50 mass ppm or less, the steel sheet having a component composition and a microstructure, wherein the component composition contains, in mass %, C: 0.150 to 0.500%, Si: 0.01 to 3.00%, Mn: 1.50 to 4.00%, P: 0.100% or less, S: 0.0200% or less, Al: 0.100% or less, N: 0.0100% or less, and O: 0.0100% or less, with the balance being Fe and inevitable impurities, and wherein in the microstructure, the total area ratio of tempered martensite and bainite is 55 to 95%, the average grain size of retained austenite is 5.0 μm or less, and the carbon concentration is greater than 0.1 mass % and is 0.3 mass % or less. 1 The area ratio of S is 50.0% or more and the carbon concentration is 0.5% by mass or more. 2 The area ratio is less than 10.0%.
[0020] [2] The high-strength steel sheet according to [1], wherein the chemical composition further contains, in mass %, at least one element selected from the group consisting of B: 0.0100% or less, Ti: 0.200% or less, Nb: 0.200% or less, V: 0.200% or less, W: 0.100% or less, Mo: 1.000% or less, Cr: 1.000% or less, Sb: 0.200% or less, Sn: 0.200% or less, Zr: 0.1000% or less, Te: 0.100% or less, Cu: 1.000% or less, Ni: 1.000% or less, Ca: 0.0100% or less, Mg: 0.0100% or less, REM: 0.0100% or less, Co: 0.010% or less, Ta: 0.10% or less, Hf: 0.10% or less, and Bi: 0.200% or less.
[0021] [3] The high-strength steel sheet according to [1] or [2], further comprising a plating layer on the surface of the steel sheet.
[0022] [4] The high-strength steel sheet according to [3] above, wherein the coating layer is a hot-dip galvanized layer, an alloyed hot-dip galvanized layer, or an electrogalvanized layer.
[0023] [5] A method for manufacturing a high-strength steel sheet, which is a method for manufacturing the high-strength steel sheet described in [1] above, wherein a steel billet having the component composition described in [1] above is hot rolled to obtain a hot-rolled steel sheet, the hot-rolled steel sheet is cold rolled to obtain a cold-rolled steel sheet, the cold-rolled steel sheet is heated at a heating temperature T1 of 750 to 950°C for 10 to 500 seconds, cooled to a cooling stop temperature T2 of 120°C or more and less than 280°C, and then heated to a reheating temperature T3 of 280 to 400°C, and then re-cooled without being held at the reheating temperature T3, wherein a heat influence index P from the reheating temperature T3 to (T3-30)°C represented by the following formula (1) is 4000 to 6200.
[0024] P=T3(log(5t)+12) …(1)
[0025] In the above formula (1), t is the cooling time from the above reheating temperature T3 to (T3-30)°C, and the unit is s.
[0026] [6] A method for manufacturing a high-strength steel sheet, which is a method for manufacturing the high-strength steel sheet described in [2] above, wherein a steel billet having the component composition described in [2] above is hot rolled to obtain a hot-rolled steel sheet, the hot-rolled steel sheet is cold rolled to obtain a cold-rolled steel sheet, the cold-rolled steel sheet is heated at a heating temperature T1 of 750 to 950°C for 10 to 500 seconds, cooled to a cooling stop temperature T2 of 120°C or more and less than 280°C, and then heated to a reheating temperature T3 of 280 to 400°C, and then re-cooled without being held at the reheating temperature T3, wherein a heat influence index P from the reheating temperature T3 to (T3-30)°C represented by the following formula (1) is 4000 to 6200.
[0027] P=T3(log(5t)+12) …(1)
[0028] In the above formula (1), t is the cooling time from the above reheating temperature T3 to (T3-30)°C, and the unit is s.
[0029] [7] The method for producing a high-strength steel sheet according to [5] or [6] above, wherein the cold-rolled steel sheet is subjected to a plating treatment.
[0030] [8] The method for producing a high-strength steel sheet according to [7] above, wherein the coating treatment is hot-dip galvanizing, alloyed hot-dip galvanizing or electrogalvanizing.
[0031] [9] A member formed using the high-strength steel sheet according to any one of [1] to [4] above.
[0032]
[10] A method for manufacturing a component, comprising: subjecting the high-strength steel sheet according to any one of [1] to [4] above to at least one of a forming process and a joining process to obtain the component.
[0033] Effects of the Invention
[0034] According to the present invention, it is possible to provide a high-strength steel sheet having a yield strength of 800 MPa or more and excellent in collision resistance and fracture resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is a diagram showing an example of heat treatment.
[0036] Figure 2A is a cross-sectional view showing a cap member.
[0037] Figure 2B : is a schematic diagram showing a cap member provided for a three-point bending test. DETAILED DESCRIPTION
[0038] [High-strength steel plate]
[0039] The high-strength steel sheet according to the present embodiment (hereinafter also referred to as “the present high-strength steel sheet”) includes a steel sheet, and as described later, may further include a plating layer on the surface of the steel sheet.
[0040] The steel sheet included in the present high-strength steel sheet has a component composition and a microstructure described below, and satisfies the amount of diffusible hydrogen in steel described below.
[0041] High strength means that the yield strength (YS) is 800 MPa or more.
[0042] The high-strength steel sheet has a yield strength of 800 MPa or more and is excellent in collision resistance and fracture resistance. Therefore, since the strength against collision is sufficient, it is suitable for use as a component of transportation vehicles such as automobiles.
[0043] As a method of forming the present high-strength steel sheet, general processing methods such as press working can be used without limitation. As a method of welding the present high-strength steel sheet, general welding methods such as spot welding and arc welding can be used without limitation.
[0044] <Steel Plate>
[0045] First, the steel sheet included in the present high-strength steel sheet will be described.
[0046] The thickness of the steel plate is not particularly limited, and is, for example, 0.5 mm or more and 3.0 mm or less.
[0047] 《Ingredients》
[0048] The chemical composition of the steel sheet included in the present high-strength steel sheet (hereinafter, also referred to as “present chemical composition” for convenience) will be described.
[0049] Unless otherwise specified, "%" in the present component composition means "mass %".
[0050] (C: 0.150~0.500%)
[0051] C generates martensite and increases the strength of the steel sheet. When the amount of C is too small, the total area ratio of tempered martensite and bainite decreases, so the collision resistance and yield strength decrease. Therefore, the amount of C is 0.150% or more, preferably 0.180% or more, and more preferably 0.200% or more.
[0052] On the other hand, when the amount of C is too high, the hard tissue with high carbon concentration (S 2 ) increases, which becomes the starting point of cracks during collision, and the fracture resistance deteriorates. Therefore, the C content is 0.500% or less, preferably 0.460% or less, and more preferably 0.400% or less.
[0053] (Si: 0.01~3.00%)
[0054] Si suppresses the formation of carbides during heat treatment and increases the yield strength. From the viewpoint of obtaining good impact resistance and a yield strength of 800 MPa or more, the amount of Si is 0.01% or more, preferably 0.50% or more, and more preferably 0.80% or more.
[0055] On the other hand, when the amount of Si is too large, the carbon concentration in the retained austenite increases excessively, and the hard structure with high carbon concentration (structure S) 2 ) increases, which becomes the starting point of cracks during collision, and the fracture resistance deteriorates. Therefore, the Si amount is 3.00% or less, preferably 2.60% or less, and more preferably 2.40% or less.
[0056] (Mn: 1.50~4.00%)
[0057] Mn affects the area ratio of tempered martensite and bainite. From the viewpoint of obtaining good impact resistance and a yield strength of 800 MPa or more, the amount of Mn is 1.50% or more, preferably 1.90% or more, and more preferably 2.30% or more.
[0058] On the other hand, when the amount of Mn is too large, hard tempered martensite and bainite increase excessively, so the fracture resistance during collision deteriorates. Therefore, the amount of Mn is 4.00% or less, preferably 3.50% or less, and more preferably 3.30% or less.
[0059] (P: 0.100% or less)
[0060] P segregates at prior austenite grain boundaries and embrittles the grain boundaries, thereby deteriorating fracture resistance during collision. Therefore, the amount of P is 0.100% or less, preferably 0.030% or less, and more preferably 0.010% or less.
[0061] The lower limit of the amount of P is not particularly limited, but P is a solid solution strengthening element and increases the strength of the steel sheet, so it is preferably 0.001%, more preferably 0.002%, and even more preferably 0.003%.
[0062] (S: 0.0200% or less)
[0063] S combines with Mn to form coarse MnS, which becomes the starting point of cracks during collision, and deteriorates the fracture resistance during collision. Therefore, the S content is 0.0200% or less, preferably 0.0100% or less, and more preferably 0.0020% or less.
[0064] The lower limit of the amount of S is not particularly limited, but is preferably 0.0001%, more preferably 0.0002%, and further preferably 0.0003% due to restrictions in production technology.
[0065] (Al: 0.100% or less)
[0066] Al acts as a deoxidizer. When the amount of Al is too much, oxides and nitrides aggregate and coarsen, thereby becoming the starting point of cracks during collision, and the fracture resistance during collision deteriorates. Therefore, the amount of Al is 0.100% or less, preferably 0.080% or less, and more preferably 0.060% or less.
[0067] The lower limit of the amount of Al is not particularly limited, but is, for example, 0.010%, preferably 0.020%, from the viewpoint of suppressing the formation of carbides during heat treatment and promoting the formation of retained austenite.
[0068] (N: 0.0100% or less)
[0069] N combines with Ti to form TiN. When the amount of N is too much, the amount of TiN formed increases, which becomes the starting point of cracks during collision, and the fracture resistance during collision deteriorates. Therefore, the amount of N is 0.0100% or less, preferably 0.0080% or less, and more preferably 0.0060% or less.
[0070] The lower limit of the amount of N is not particularly limited, but is preferably 0.0001%, more preferably 0.0003%, and further preferably 0.0005% due to restrictions in production technology.
[0071] (O: 0.0100% or less)
[0072] O forms oxides, and the formed oxides become the starting point of cracks during collision, and the fracture resistance during collision is deteriorated. Therefore, the amount of O is 0.0100% or less, preferably 0.0050% or less, and more preferably 0.0020% or less.
[0073] (Other elements)
[0074] The present component composition may further contain, in mass %, at least one element selected from the group consisting of the elements described below.
[0075] ((B: 0.0100% or less))
[0076] B is an element that can improve the hardenability of the steel sheet by segregating at the austenite grain boundary, and it is preferably added because it increases the yield strength of the steel sheet.
[0077] However, when the amount of B is too much, Fe 23 (CB) 6 , which becomes the starting point of cracks during collision, and the fracture resistance during collision is deteriorated. Therefore, the B content is preferably 0.0100% or less, more preferably 0.0050% or less, further preferably 0.0040% or less, and particularly preferably 0.0030% or less.
[0078] The lower limit of the amount of B is not particularly limited, but from the viewpoint of obtaining the effect of adding B, it is, for example, 0.0005%, preferably 0.0010%.
[0079] ((Ti: 0.200% or less))
[0080] Ti forms fine carbides, nitrides, or carbonitrides during hot rolling or heat treatment, thereby increasing the yield strength of the steel sheet, and therefore, it is preferably added.
[0081] However, when the amount of Ti is too large, it combines with N to form coarse nitrides, thereby deteriorating the fracture resistance during collision. Therefore, the amount of Ti is preferably 0.200% or less, more preferably 0.100% or less, and further preferably 0.050% or less.
[0082] The lower limit of the amount of Ti is not particularly limited, but from the viewpoint of obtaining the effect of adding Ti, it is, for example, 0.005%, preferably 0.010%.
[0083] ((Nb: 0.200% or less, V: 0.200% or less, W: 0.100% or less))
[0084] Nb, V, and W form fine carbides, nitrides, or carbonitrides during hot rolling or heat treatment, thereby increasing the yield strength of the steel sheet, and therefore, are preferably added.
[0085] However, when these elements are added in excessive amounts, they do not melt when the steel slab is heated but remain as coarse carbides. Coarse carbides become the starting point of cracks during collision, and the fracture resistance during collision is deteriorated.
[0086] Therefore, the amount of Nb is preferably 0.200% or less, more preferably 0.100% or less, and still more preferably 0.050% or less. The lower limit is not particularly limited, but from the viewpoint of obtaining the effect of Nb addition, it is, for example, 0.005%, preferably 0.010%.
[0087] The amount of V is preferably 0.200% or less, more preferably 0.100% or less, and still more preferably 0.050% or less. The lower limit is not particularly limited, but from the viewpoint of obtaining the effect of V addition, it is, for example, 0.005%, preferably 0.010%.
[0088] The amount of W is preferably 0.100% or less, more preferably 0.080% or less, and still more preferably 0.050% or less. The lower limit is not particularly limited, but from the viewpoint of obtaining the effect of W addition, it is, for example, 0.010%, preferably 0.020%.
[0089] ((Mo: 1.000% or less, Cr: 1.000% or less))
[0090] Mo and Cr are preferably added because they increase the yield strength of the steel sheet by improving the hardenability of the steel sheet. However, when the amount of these elements is too large, hard martensite is excessively generated, and the fracture resistance during collision is deteriorated.
[0091] Therefore, the amount of Mo is preferably 1.000% or less, more preferably 0.800% or less, and still more preferably 0.500% or less. The lower limit is not particularly limited, but from the viewpoint of obtaining the effect of Mo addition, it is, for example, 0.010%, preferably 0.020%.
[0092] The Cr content is preferably 1.000% or less, more preferably 0.800% or less, and still more preferably 0.500% or less. The lower limit is not particularly limited, but from the viewpoint of obtaining the effect of Cr addition, it is, for example, 0.010%, preferably 0.020%.
[0093] ((Sb: 0.200% or less, Sn: 0.200% or less))
[0094] Sb and Sn are preferably added because they suppress decarburization on the surface of the steel sheet and increase the yield strength of the steel sheet. However, when the amount of these elements is too large, the steel becomes brittle and the fracture resistance during collision deteriorates.
[0095] Therefore, the amount of Sb is preferably 0.200% or less, more preferably 0.080% or less, and still more preferably 0.040% or less. The lower limit is not particularly limited, but from the viewpoint of obtaining the effect of Sb addition, it is, for example, 0.001%, preferably 0.002%.
[0096] The amount of Sn is preferably 0.200% or less, more preferably 0.080% or less, and still more preferably 0.040% or less. The lower limit is not particularly limited, but from the viewpoint of obtaining the effect of Sn addition, it is, for example, 0.001%, preferably 0.002%.
[0097] ((Zr: 0.1000% or less, Te: 0.100% or less))
[0098] Zr and Te make the shapes of nitrides and sulfides spherical and improve the fracture resistance during collision, so they are preferably added. However, when the amount of these elements is too large, the coarse precipitates remaining due to not being dissolved during the heating of the hot-rolled steel billet increase, and the fracture resistance during collision deteriorates.
[0099] Therefore, the amount of Zr is preferably 0.1000% or less, more preferably 0.0800% or less, and still more preferably 0.0500% or less. The lower limit is not particularly limited, but from the viewpoint of obtaining the effect of adding Zr, it is, for example, 0.0050%, preferably 0.0100%.
[0100] The amount of Te is preferably 0.100% or less, more preferably 0.080% or less, and still more preferably 0.050% or less. The lower limit is not particularly limited, but from the viewpoint of obtaining the effect of adding Te, it is, for example, 0.005%, preferably 0.010%.
[0101] (Cu: 1.000% or less)
[0102] Cu is preferably added because it increases the yield strength of the steel sheet by improving the hardenability of the steel sheet. However, when the amount of Cu is too large, the fracture resistance during collision deteriorates due to the increase in Cu inclusions.
[0103] Therefore, the amount of Cu is preferably 1.000% or less, more preferably 0.800% or less, and still more preferably 0.500% or less. The lower limit is not particularly limited, but from the viewpoint of obtaining the effect of Cu addition, it is, for example, 0.010%, preferably 0.020%.
[0104] ((Ni: 1.000% or less))
[0105] Ni is preferably added because it increases the yield strength of the steel sheet by improving the hardenability of the steel sheet. However, when the amount of Ni is too large, the fracture resistance during collision deteriorates due to an increase in hard martensite.
[0106] Therefore, the amount of Ni is preferably 1.000% or less, more preferably 0.800% or less, and still more preferably 0.500% or less. The lower limit is not particularly limited, but from the viewpoint of obtaining the effect of Ni addition, it is, for example, 0.010%, preferably 0.020%.
[0107] (Ca: 0.0100% or less, Mg: 0.0100% or less, REM: 0.0100% or less))
[0108] Ca, Mg and REM (Rare Earth Metal) are preferably added because they spheroidize the shape of precipitates such as sulfides and oxides and improve the fracture resistance during collision. However, when the amount of these elements is too large, the coarsened sulfides become the starting point of cracks during collision, and the fracture resistance during collision is deteriorated.
[0109] Therefore, the amount of Ca is preferably 0.0100% or less, more preferably 0.0050% or less, and still more preferably 0.0040% or less. The lower limit is not particularly limited, but from the viewpoint of obtaining the effect of Ca addition, it is, for example, 0.0005%, preferably 0.0010%.
[0110] The amount of Mg is preferably 0.0100% or less, more preferably 0.0050% or less, and still more preferably 0.0040% or less. The lower limit is not particularly limited, but from the viewpoint of obtaining the effect of Mg addition, it is, for example, 0.0005%, preferably 0.0010%.
[0111] The amount of REM is preferably 0.0100% or less, more preferably 0.0040% or less, and still more preferably 0.0030% or less. The lower limit is not particularly limited, but from the viewpoint of obtaining the effect of adding REM, it is, for example, 0.0005%, preferably 0.0010%.
[0112] ((Co: 0.010% or less, Ta: 0.10% or less, Hf: 0.10% or less, Bi: 0.200% or less))
[0113] Co, Ta, Hf and Bi make the shape of the precipitate spherical and improve the fracture resistance during collision, so it is preferably added. However, when the amount of these elements is too much, the coarsened precipitate becomes the starting point of cracks during collision, and the fracture resistance during collision deteriorates.
[0114] Therefore, the amount of Co is preferably 0.010% or less, more preferably 0.008% or less, and still more preferably 0.007% or less. The lower limit is not particularly limited, but from the viewpoint of obtaining the effect of Co addition, it is, for example, 0.001%, preferably 0.002%.
[0115] The amount of Ta is preferably 0.10% or less, more preferably 0.08% or less, and still more preferably 0.07% or less. The lower limit is not particularly limited, but from the viewpoint of obtaining the effect of Ta addition, it is, for example, 0.01%, preferably 0.02%.
[0116] The amount of Hf is preferably 0.10% or less, more preferably 0.08% or less, and still more preferably 0.07% or less. The lower limit is not particularly limited, but from the viewpoint of obtaining the effect of Hf addition, it is, for example, 0.01%, preferably 0.02%.
[0117] The Bi content is preferably 0.200% or less, more preferably 0.100% or less, and still more preferably 0.080% or less. The lower limit is not particularly limited, but from the viewpoint of obtaining the effect of adding REM, it is, for example, 0.001%, preferably 0.005%.
[0118] (margin)
[0119] The balance in this component composition is composed of Fe and inevitable impurities.
[0120] Microstructure
[0121] Next, the microstructure of the steel sheet included in the present high-strength steel sheet (hereinafter, also referred to as “the present microstructure” for convenience) will be described.
[0122] In order to obtain the effects of the present invention, it is not sufficient to satisfy only the above-mentioned present component composition, and it is also necessary to satisfy the present microstructure described below.
[0123] Hereinafter, the area ratio refers to the area ratio relative to the entire microstructure. The area ratio of each structure is obtained by the method described in the Examples described below.
[0124] (Total area ratio of tempered martensite and bainite: 55-95%)
[0125] From the viewpoint of stably ensuring good impact resistance and yield strength, the total area ratio of tempered martensite and bainite is 55% or more, preferably 58% or more, and more preferably 60% or more.
[0126] On the other hand, when the total area ratio of tempered martensite and bainite is too high, the hard structure with high carbon concentration (structure S 2 ) increases, which becomes the starting point of cracks during collision, and the fracture resistance deteriorates. Therefore, the total area ratio is 95% or less, preferably 92% or less, and more preferably 88% or less.
[0127] (Average grain size of retained austenite: 5.0 μm or less)
[0128] When stress is repeatedly applied to the steel sheet, the retained austenite transforms into hard martensite due to work hardening. If the retained austenite is too large, the martensite transformed from the retained austenite becomes the starting point of cracks during collision, and the fracture resistance deteriorates.
[0129] Therefore, the average grain size of retained austenite is 5.0 μm or less, preferably 4.0 μm or less, more preferably 3.0 μm or less, further preferably 2.0 μm or less, and particularly preferably 1.0 μm or less.
[0130] (Organization S 1 Area ratio: 50.0% or more)
[0131] The structure with low carbon concentration has high toughness and high fracture resistance. In addition, the structure with low carbon concentration contains at least a part of retained austenite. The retained austenite with low carbon concentration is easy to undergo martensitic transformation. When the steel plate is repeatedly loaded with stress, the retained austenite with low carbon concentration undergoes martensitic transformation, thereby greatly dispersing the strain during collision, and the generation of cracks during collision can be suppressed. That is, the fracture resistance is improved.
[0132] Therefore, the carbon concentration of the structure S is greater than 0.1 mass % and less than 0.3 mass %. 1 The area ratio is 50.0% or more, preferably 55.0% or more, more preferably 60.0% or more.
[0133] On the other hand, organization S 1 The upper limit of the area ratio is not particularly limited, and is, for example, 90.0%, preferably 95.0%.
[0134] (Organization S 2 Area ratio: less than 10.0%)
[0135] Since a structure with a high carbon concentration is hard, it becomes a starting point of cracks during collision, and the fracture resistance is deteriorated.
[0136] Therefore, the carbon concentration of the structure S is 0.5 mass % or more. 2 The area ratio is 10.0% or less, preferably 8.0% or less, and more preferably 7.0% or less.
[0137] (Residual Organization)
[0138] The present microstructure may include structures other than tempered martensite, bainite and retained austenite (remaining structure).
[0139] As the residual structure, for example, fresh martensite; pearlite; ferrite; iron-based carbonitride; alloy carbonitride; MnS, Al 2 O 3 etc. inclusions; etc. well-known organizations.
[0140] The area ratio of the surplus structure is preferably 10% or less, more preferably 8% or less, and further preferably 5% or less. When the area ratio of the surplus structure is within this range, the effect of the present invention is not impaired.
[0141] 《Diffusible hydrogen content in steel: 0.50 mass ppm or less》
[0142] If the amount of diffusible hydrogen in steel is too high, delayed fracture occurs and fracture resistance deteriorates. Therefore, the amount of diffusible hydrogen in steel is 0.50 mass ppm or less, preferably 0.30 mass ppm or less, and more preferably 0.20 mass ppm or less.
[0143] The amount of diffusible hydrogen in the steel is determined by the method described in the examples described later.
[0144] <Plating>
[0145] From the viewpoint of improving corrosion resistance and the like, the high-strength steel sheet may further include a plating layer on the surface of the steel sheet.
[0146] Examples of the plating layer include a hot-dip galvanizing layer, an alloyed hot-dip galvanizing layer, and an electrogalvanizing layer. The plating layer is formed by a plating treatment described below.
[0147] [Method for producing high-strength steel sheet]
[0148] Next, a method for producing a high-strength steel sheet according to the present embodiment (hereinafter referred to as "the present production method") will be described. The present production method is also a method for producing the above-mentioned present high-strength steel sheet.
[0149] Unless otherwise specified, the temperature when heating or cooling the steel billet, steel plate, etc. shown below refers to the surface temperature of the steel billet, steel plate, etc.
[0150] The method for producing molten steel to become a steel billet (steel raw material) is not particularly limited, and a known method using a converter, an electric furnace, etc. can be adopted. Preferably, the steel billet is obtained from the molten steel by a continuous casting method. The steel billet can also be obtained by other methods such as an ingot casting-blowing rolling method and a thin slab continuous casting method.
[0151] <Hot rolling>
[0152] In the present production method, first, a steel slab having the above-mentioned present component composition is hot-rolled to obtain a hot-rolled steel sheet.
[0153] When hot rolling is performed, the steel slab may be reheated in a heating furnace before rolling. When the steel slab is kept at a temperature higher than a predetermined temperature, direct rolling may be performed without heating the steel slab.
[0154] In hot rolling, the steel slab is subjected to rough rolling and finish rolling.
[0155] It is preferred that the steel slab be heated before rough rolling to melt the carbides in the steel slab.
[0156] From the viewpoint of dissolving carbides or preventing an increase in rolling load, the temperature at which the billet is heated (billet heating temperature) is preferably 1100° C. or higher, more preferably 1150° C. or higher.
[0157] On the other hand, from the viewpoint of preventing an increase in scale loss, the slab heating temperature is preferably 1300° C. or lower, more preferably 1280° C. or lower.
[0158] As described above, when the steel slab before rough rolling is maintained at a temperature equal to or higher than a predetermined temperature and carbides in the steel slab are melted, heating of the steel slab before rough rolling can be omitted.
[0159] The conditions for rough rolling and finish rolling are not particularly limited. For example, the finish rolling end temperature is preferably 700 to 1100°C, more preferably 800 to 1000°C.
[0160] <Cold Rolling>
[0161] Next, the hot-rolled steel sheet is cold-rolled to obtain a cold-rolled steel sheet.
[0162] The rolling reduction rate of cold rolling is preferably 30% or more, more preferably 35% or more. The upper limit is not particularly limited, but is, for example, 70% or less, preferably 65% or less.
[0163] <Heat Treatment>
[0164] Next, the cold-rolled steel sheet obtained by cold rolling is subjected to heat treatment.
[0165] Figure 1 This is a diagram showing an example of heat treatment.
[0166] In the heat treatment, in short, the cold-rolled steel sheet is heated at a heating temperature T1, cooled to a cooling stop temperature T2, and then reheated to a reheating temperature T3, and recooled without being held at the reheating temperature T3. During the recooling, the cold-rolled steel sheet is cooled from the reheating temperature T3 to at least (T3-30)°C.
[0167] In addition, the cold-rolled steel sheet subjected to heat treatment corresponds to the steel sheet included in the above-mentioned present high-strength steel sheet.
[0168] 《Heating temperature T1: 750~950℃, heating time t 1 :10~500s》
[0169] First, the cold-rolled steel sheet is heated at a heating temperature T1.
[0170] At this time, the heating temperature T1 is too low, or the heating time t 1If (the time for holding the cold-rolled steel sheet at the heating temperature T1) is too short, heating is performed in a dual phase region of ferrite and austenite. In this case, the final microstructure contains ferrite, and the total area ratio of tempered martensite and bainite is reduced, making it difficult to ensure good collision resistance and yield strength.
[0171] Therefore, the heating temperature T1 is 750° C. or higher, preferably 800° C. or higher, and more preferably 850° C. or higher. 1 It is 10 s or longer, preferably 50 s or longer, and more preferably 80 s or longer.
[0172] On the other hand, when the heating temperature T1 is too high, the average grain size of the retained austenite tends to become coarse, so the fracture resistance decreases. In addition, due to the increase in hydrogen partial pressure, the amount of hydrogen intruding into the steel increases, so the amount of diffusible hydrogen in the steel increases.
[0173] In addition, the heating time t 1 When the length is too long, the average grain size of retained austenite tends to become coarse, so the fracture resistance decreases.
[0174] Therefore, the heating temperature T1 is 950° C. or lower, preferably 930° C. or lower, and more preferably 900° C. or lower. 1 It is 500 s or less, preferably 300 s or less, and more preferably 200 s or less.
[0175] 《Cooling stop temperature T2: 120℃ or higher and lower than 280℃》
[0176] Next, the cold-rolled steel sheet heated at the heating temperature T1 is cooled to a cooling stop temperature T2.
[0177] When the cooling stop temperature T2 is too low, the total area ratio of tempered martensite and bainite increases, and the high carbon concentration structure (structure S 2 ) increases, so the fracture resistance deteriorates.
[0178] Therefore, the cooling stop temperature T2 is 120°C or higher, preferably 140°C or higher, and more preferably 150°C or higher.
[0179] On the other hand, when the cooling stop temperature T2 is too high, the total area ratio of tempered martensite and bainite decreases, so that good impact resistance and yield strength cannot be stably ensured.
[0180] Therefore, the cooling stop temperature T2 is lower than 280°C, preferably 270°C or lower, and more preferably 260°C or lower.
[0181] 《Reheating temperature T3: 280~400℃》
[0182] Next, the cold-rolled steel sheet cooled to the cooling stop temperature T2 is reheated to the reheating temperature T3, and is recooled without being held at the reheating temperature T3.
[0183] At this time, if the reheating temperature T3 is too low, the low carbon concentration structure (structure S 1 ) decreases and the fracture resistance deteriorates.
[0184] Therefore, the reheating temperature T3 is 280°C or higher, preferably 290°C or higher, and more preferably 300°C or higher.
[0185] On the other hand, when the reheating temperature T3 is too high, a large amount of iron carbides precipitate in the tempered martensite, the total area ratio of the tempered martensite and bainite decreases, the yield strength decreases, and the impact resistance decreases.
[0186] Therefore, the reheating temperature T3 is 400°C or lower, preferably 380°C or lower, and more preferably 350°C or lower.
[0187] 《Heat impact index P: 4000~6200》
[0188] As described above, the cold-rolled steel sheet reheated to the reheating temperature T3 is re-cooled without being held at the reheating temperature T3.
[0189] During the recooling, the cold-rolled steel sheet is cooled from the reheating temperature T3 to at least (T3-30)° C. At this time, the heat influence index P for the cold-rolled steel sheet from the reheating temperature T3 to (T3-30)° C. is represented by the following formula (1).
[0190] P=T3(log(5t)+12) …(1)
[0191] In the above formula (1), t is the cooling time (unit: s) from the reheating temperature T3 to (T3-30)°C.
[0192] The carbon concentration of each structure constituting the microstructure can be controlled by the heat influence index P.
[0193] That is, in the temperature range from the reheating temperature T3 to (T3-30)°C, the solid solution carbon in the martensite as the parent phase is diffused into the untransformed austenite.
[0194] When the heat influence index P is too low, the solid solution carbon in the martensite is not fully diffused into the untransformed austenite, and the high carbon concentration structure (structure S 2 ) increases, low carbon concentration tissue (tissue S 1 Therefore, the heat impact index P is 4000 or more, preferably 4200 or more, and more preferably 4400 or more.
[0195] On the other hand, when the heat influence index P is too high, the dissolved carbon in the untransformed austenite becomes excessive, so the high carbon concentration structure (structure S) is more concentrated in the final microstructure. 2 )Increase.
[0196] Therefore, the heat impact index P is 6000 or less, preferably 5800 or less, and more preferably 5500 or less.
[0197] <Plating treatment>
[0198] In the present production method, a plating layer can be formed on the surface of the re-cooled cold-rolled steel sheet by subjecting the re-cooled cold-rolled steel sheet to a plating treatment.
[0199] Examples of the plating layer include a hot-dip galvanizing layer, an alloyed hot-dip galvanizing layer, and an electrogalvanizing layer.
[0200] The plating treatment is preferably hot-dip galvanizing, alloy hot-dip galvanizing or electrogalvanizing.
[0201] When the hot-dip galvanizing treatment is performed, an apparatus configured to continuously perform the above-mentioned heat treatment and the hot-dip galvanizing treatment can be used.
[0202] When hot-dip galvanizing is performed, for example, the steel sheet is immersed in a zinc bath at a bath temperature of 440 to 500° C. Then, the coating weight is preferably adjusted by gas wiping or the like.
[0203] The zinc bath preferably has a composition in which the Al content is 0.10 to 0.23% by mass and the balance is Zn and unavoidable impurities.
[0204] When performing alloying hot-dip galvannealing, when the alloying temperature is too low, the Zn-Fe alloying rate sometimes becomes too slow, and alloying becomes significantly difficult. On the other hand, when the alloying temperature is too high, the untransformed austenite sometimes transforms into pearlite. Therefore, the alloying temperature is preferably 450 to 600°C, more preferably 470 to 550°C, and further preferably 470 to 530°C.
[0205] When the electrogalvanizing treatment is performed, an apparatus configured to continuously perform the above-mentioned heat treatment and the electrogalvanizing treatment can be used.
[0206] The electrogalvanizing treatment is performed to form an electrogalvanized layer.
[0207] The electrogalvanized layer is not particularly limited, and a conventionally known electrogalvanized layer is preferably used. The electrogalvanized layer may be a zinc alloy plating layer in which an appropriate amount of Fe, Cr, Ni, Mn, Co, Sn, Pb, or Mo is added to Zn according to the purpose.
[0208] The coating weight of hot-dip galvanized steel sheet (GI), alloyed hot-dip galvanized steel sheet (GA) and electrogalvanized steel sheet (EG) is preferably 20 to 80 g / m per side. 2 (Both sides plated).
[0209] The plated steel sheet is cooled to a temperature of, for example, 50° C. or less. The steel sheet cooled to a temperature of 50° C. or less may be rolled at an elongation of 0.05 to 1.00%. The elongation is preferably 0.08 to 0.70%.
[0210] The rolling can be carried out on a device that is continuous with a device (plating device) for implementing a galvanizing treatment, or on a device that is discontinuous with the plating device. In addition, the target elongation can be achieved by one rolling, or the target elongation can be achieved by rolling twice or more.
[0211] In addition, the rolling described here generally refers to skin temper rolling, but as long as the same elongation as skin temper rolling can be given, rolling by processing using a leveler or the like may also be used.
[0212] In the present manufacturing method, for example, the holding temperature such as the heating temperature and the reheating temperature may not be constant as long as they are within the above temperature range. The cooling rate may also be changed during cooling as long as it is within the above speed range. As long as the above temperature range and other conditions are met, the heat treatment may be performed with any equipment.
[0213] [member]
[0214] Next, the components of the present embodiment (hereinafter also referred to as “present components”) will be described.
[0215] The present member is a member at least partly formed using the present high-strength steel sheet described above, and is, for example, a member formed by forming the present high-strength steel sheet into a target shape by processing (press processing, etc.).
[0216] The present member is preferably a member for automobile parts. It should be noted that the member for automobile parts may include a steel sheet other than the present high-strength steel sheet as a raw material.
[0217] As described above, the high-strength steel sheet has a yield strength of 800 MPa or more and is excellent in collision resistance and fracture resistance. Therefore, the member has excellent collision resistance and fracture resistance and can contribute to the lightweight of the vehicle body. Therefore, among automobile parts, it is particularly suitable as all members used as automobile skeleton structural parts or automobile reinforcement parts.
[0218] [Method of manufacturing component]
[0219] Next, a method for producing the present member will be described.
[0220] The present member is obtained, for example, by subjecting the present high-strength steel sheet to at least one of a forming process and a joining process.
[0221] The forming process is not particularly limited, and examples thereof include press working and the like.
[0222] The joining process is not particularly limited, and examples thereof include general welding such as spot welding and arc welding, and riveting using rivets or the like.
[0223] Example
[0224] Hereinafter, the present invention will be described in detail with reference to Examples, but the present invention is not limited to the Examples described below.
[0225] <Manufacturing of Steel Plate>
[0226] Molten steel having the composition shown in Table 1 below, with the balance being Fe and inevitable impurities, was produced by a converter, and steel slabs were obtained by continuous casting. The underlined parts in Table 1 below are outside the scope of the present invention (the same applies to Tables 2 and 3 described below).
[0227] The obtained steel slab was hot rolled under the conditions shown in the following Table 2 to obtain a hot rolled steel sheet. Specifically, the steel slab was heated to 1250°C, rough rolled, and then finish rolled at a finish rolling end temperature of 900°C.
[0228] The obtained hot-rolled steel sheets were cold-rolled at the rolling ratios shown in Table 2 below, thereby obtaining cold-rolled steel sheets (sheet thickness: 1.2 mm).
[0229] The obtained cold-rolled steel sheets were subjected to heat treatment under the conditions shown in Table 2 below.
[0230] In some examples, both surfaces of a cold-rolled steel sheet (CR) after heat treatment are plated to obtain a galvanized steel sheet (GI), a galvannealed steel sheet (GA), or an electrogalvanized steel sheet (EG).
[0231] As the hot-dip galvanizing bath, a zinc bath containing Al: 0.20 mass % and the balance consisting of Zn and inevitable impurities is used when manufacturing GI, and a zinc bath containing Al: 0.14 mass % and the balance consisting of Zn and inevitable impurities is used when manufacturing GA.
[0232] The bath temperature was set to 470° C. in the case of producing both GI and GA.
[0233] The coating weight is set to 45 to 72 g / m per side when manufacturing GI. 2 When manufacturing GA, set it to 45g / m per single side. 2 .
[0234] In the case of producing GA, the alloying temperature was set to 500°C.
[0235] The composition of the GI plating layer contains Fe: 0.1-1.0 mass%, Al: 0.2-1.0 mass%, and the balance is Fe and inevitable impurities. The composition of the GA plating layer contains Fe: 7-15 mass%, Al: 0.1-1.0 mass%, and the balance is Fe and inevitable impurities.
[0236] When manufacturing EG, an electrogalvanizing line is used with a coating weight of 30 g / m per side. 2 The electro-galvanizing treatment is carried out in the manner of
[0237] Hereinafter, the cold-rolled steel sheet (CR), the hot-dip galvanized steel sheet (GI), the alloyed hot-dip galvanized steel sheet (GA) and the electrogalvanized steel sheet (EG) after heat treatment are also referred to as "steel sheets".
[0238] <Observation of Microstructure>
[0239] The microstructure of the obtained steel plate was observed as follows. The results are shown in the following Table 3. In addition, in the following Table 3, martensite is expressed as "M", bainite is expressed as "B", and austenite is expressed as "γ".
[0240] 《Total area ratio of tempered martensite and bainite》
[0241] The obtained steel plate was polished so that the cross section (L cross section) at the 1 / 4 position of the plate thickness and parallel to the rolling direction was used as the observation surface. The observation surface was corroded with 1 vol % nitric acid solution and observed with a scanning electron microscope (SEM) at a magnification of 3000 times.
[0242] The observation surface was observed in 10 fields to obtain a SEM image, and the obtained SEM image was analyzed to determine the total area ratio (unit: %) of tempered martensite and bainite.
[0243] More specifically, dark gray portions in the obtained SEM images were determined to be tempered martensite and bainite, and their area ratios (average area ratios of 10 fields of view) were determined. In the analysis of the SEM images, Image-Pro manufactured by MediaCybernetics was used as analysis software.
[0244] 《Average grain size in retained austenite》
[0245] For the obtained steel plate, the cross section (L cross section) parallel to the rolling direction is used as the observation surface. After grinding, it is polished and ground using a colloidal silica solution. Then, by the EBSD method (acceleration voltage of the electron beam: 15 kV, step interval: 0.04 μm), 10 areas of 50 μm×50 μm in the observation surface are measured to obtain data for obtaining a tissue image. The obtained data is processed using the OIM Analysis software manufactured by TSL to obtain a tissue image. For the obtained tissue image, Image-Pro of Media Cybernetics is used to determine the area of each retained austenite grain and calculate the equivalent circle diameter. Their average value is taken as the average grain size of the retained austenite (unit: μm).
[0246] Organization S 1 and organization S 2 Area ratio
[0247] The obtained steel plate was polished with diamond paste in a manner that the cross section (L cross section) parallel to the rolling direction was the observation surface. The observation surface was finished into a mirror surface by alumina polishing, and then, in order to eliminate hydrocarbon contamination (carbon contamination, hereinafter referred to as "contamination") on the observation surface, it was cleaned using a plasma cleaner.
[0248] For the cleaned observation surface, an electron beam microanalyzer (FE-EPMA: Field Emission Electron Probe Micro Analyzer) equipped with a field emission electron gun is used to obtain data for obtaining an element mapping image. The measurement conditions are set to an acceleration voltage of 7 kV and a current of 50 nA according to the non-patent literature (T. Yamashita, Y. Tanaka, M. Nagoshi and K. Ishida: Sci. Rep., 6 (2016), DOI: 10.1038 / srep29825.). At this time, the steel plate used as a sample is heated and maintained at 100 ° C, and the measurement is performed under non-contamination conditions. The measured data is converted into carbon concentration by the calibration method to obtain an element mapping image of carbon.
[0249] The measurement using FE-EPMA was performed 30 times for each steel plate, and an element mapping image was obtained each time.
[0250] The ratio (area ratio) of the area with a carbon concentration of more than 0.1 mass % and less than 0.3 mass % to the total area of the obtained elemental mapping image was calculated, and the average value of 30 times was taken as the structure S. 1 Area ratio (unit: %).
[0251] Similarly, the ratio (area ratio) of the area with a carbon concentration of 0.5 mass % or more to the total area of the obtained elemental mapping image was calculated, and the average value of 30 times was taken as the structure S. 2 Area ratio (unit: %).
[0252] <Determination of Diffusible Hydrogen Amount in Steel>
[0253] A test piece with a length of 30 mm and a width of 5 mm was cut from the obtained steel plate. The amount of diffusible hydrogen in the steel was measured by the temperature rise desorption analysis method for the cut test piece. The heating rate was set to 200°C / hour. The cumulative value of the amount of hydrogen detected in the temperature range from room temperature (25°C) to below 210°C was taken as the amount of diffusible hydrogen in the steel (unit: mass ppm).
[0254] The plated steel sheet was measured in the same manner after the plated steel sheet was removed using a router (precision grinder).
[0255] The results are shown in the following Table 3. The amount of diffusible hydrogen in the steel is preferably 0.50 mass ppm or less.
[0256] <Evaluation>
[0257] The obtained steel sheets were evaluated by the following methods. The results are shown in Table 3 below.
[0258] Tensile test
[0259] From the obtained steel plate, a No. 5 test piece described in JIS Z 2241 was cut out with the direction at 90° to the rolling direction as the longitudinal direction (tensile direction). Using the cut test piece, a tensile test according to JIS Z 2241 was performed 5 times, and the yield strength (YS) was calculated from the average value of the 5 times.
[0260] When YS is 800 MPa or more, it can be evaluated as high strength.
[0261] 《Collision Endurance Evaluation Test》
[0262] A member (hat member) having a hat-shaped cross section was produced using the obtained steel plate, and a three-point bending test was performed to determine the maximum load (unit: kN).
[0263] First, based on Figure 2A , the cap member 1 is described.
[0264] Figure 2A 2 is a cross-sectional view showing the cap member 1 . Figure 2A, the dimensions of the cap member 1 are shown. The cap member 1 is joined to the flat plate 2 by spot welding (nugget diameter: 4.5√t, spot spacing: 35 mm). The flat plate 2 is a cold-rolled steel plate without coating, with a tensile strength (TS) of 590 MPa and a plate thickness t that is the same as that of the cap member 1 (1.2 mm).
[0265] Next, based on Figure 2B , the three-point bending test is explained.
[0266] Figure 2B 1 is a schematic diagram showing the cap member 1 subjected to a three-point bending test. Figure 2B Various dimensions are also shown in FIG. The flat plate 2 joined to the cap member 1 is supported by the support member 3 as a rigid body. In this state, the impactor 4 as a rigid body is moved from above toward the cap member 1 at a speed of 1 m / s. In this way, a three-point bending test is implemented.
[0267] The three-point bending test was performed three times on each steel plate, and the average value of the maximum loads obtained each time was taken as the maximum load of the steel plate.
[0268] In Table 3 below, a maximum load of 40 kN or more is indicated as "◎", a maximum load of 30 kN or more and less than 40 kN is indicated as "○", and a maximum load of less than 30 kN is indicated as "×".
[0269] If it is "◎" or "○", it can be evaluated that the collision resistance is excellent.
[0270] 《Fracture resistance evaluation test》
[0271] According to JISZ 2241, a test piece (parallel portion length: 40 mm, parallel portion width: 20 mm) with the direction at 90° to the rolling direction as the length direction (tensile direction) was cut from the obtained steel plate. A machined hole with a diameter of 8 mm was formed at the center position of the length direction of the parallel portion of the test piece and the center position of the width direction of the parallel portion.
[0272] Using a test piece having a machined hole formed therein, a tensile test was performed five times at a constant tensile speed (2 mm / min) in accordance with JIS Z 2241 to determine the breaking stroke.
[0273] In Table 3 below, a breaking stroke (average value of 5 tensile tests) of 0.85 mm or more is indicated as "◎", a breaking stroke of 0.70 mm or more and less than 0.85 mm is indicated as "○", and a breaking stroke of less than 0.70 mm is indicated as "×".
[0274] If it is "◎" or "○", it can be evaluated that the fracture resistance is excellent.
[0275]
[0276]
[0277] [Table 2]
[0278]
[0279]
[0280] [Table 3]
[0281]
[0282]
[0283] <Summary of evaluation results>
[0284] As shown in Tables 1 to 3, the steel plates Nos. 1 to 10, 15 to 17, 22, 25, 30, and 33 to 42 all have a yield strength of 800 MPa or more and are excellent in impact resistance and fracture resistance.
[0285] On the other hand, the steel sheets of Nos. 11 to 14, 18 to 21, 23 to 24, 26 to 29, and 31 to 32 were insufficient in at least one of the yield strength, the impact resistance, and the fracture resistance.
Claims
1. A high-strength steel plate comprising: The steel plate has a diffusible hydrogen content of 0.50 mass ppm or less. The steel plate has a composition and a microstructure, The composition contains, in mass%, C: 0.150-0.500%, Si: 0.01-3.00%, Mn: 1.50-4.00%, P: 0.100% or less, S: 0.0200% or less, Al: 0.100% or less, N: 0.0100% or less, and O: 0.0100% or less, with the balance being Fe and inevitable impurities. In the microstructure, the total area ratio of tempered martensite and bainite is 55 to 95%, the average grain size of retained austenite is 5.0 μm or less, the area ratio of structure S1 having a carbon concentration greater than 0.1 mass % and less than 0.3 mass % is 50.0% or more, and the area ratio of structure S2 having a carbon concentration greater than 0.5 mass % is 10.0% or less.
2. The high-strength steel plate according to claim 1, wherein: The composition further comprises, by mass%, B selected from: At least one element selected from the group consisting of Ti: 0.0100% or less, Ti: 0.200% or less, Nb: 0.200% or less, V: 0.200% or less, W: 0.100% or less, Mo: 1.000% or less, Cr: 1.000% or less, Sb: 0.200% or less, Sn: 0.200% or less, Zr: 0.1000% or less, Te: 0.100% or less, Cu: 1.000% or less, Ni: 1.000% or less, Ca: 0.0100% or less, Mg: 0.0100% or less, REM: 0.0100% or less, Co: 0.010% or less, Ta: 0.10% or less, Hf: 0.10% or less, and Bi: 0.200% or less.
3. The high-strength steel sheet according to claim 1 or 2, wherein: The surface of the steel plate is further provided with a plating layer.
4. The high-strength steel plate according to claim 3, wherein: The coating is a hot-dip galvanized layer, an alloyed hot-dip galvanized layer or an electro-galvanized layer.
5. A method for producing a high-strength steel sheet, which is a method for producing the high-strength steel sheet according to claim 1, wherein: A steel slab having the component composition described in claim 1 is hot-rolled to obtain a hot-rolled steel sheet. The hot-rolled steel sheet is cold-rolled to obtain a cold-rolled steel sheet. The cold-rolled steel sheet is heated at a heating temperature T1 of 750 to 950° C. for 10 to 500 seconds, cooled to a cooling stop temperature T2 of 120° C. or higher and lower than 280° C., and then heated to a reheating temperature T3 of 280 to 400° C., and then recooled without being held at the reheating temperature T3. The heat impact index P from the reheating temperature T3 to (T3-30)°C represented by the following formula (1) is 4000 to 6200, P=T3(log(5t)+12) …(1) In the formula (1), t is the cooling time from the reheating temperature T3 to (T3-30)°C, in seconds.
6. A method for producing a high-strength steel sheet, which is a method for producing the high-strength steel sheet according to claim 2, wherein: A steel slab having the component composition described in claim 2 is hot-rolled to obtain a hot-rolled steel sheet. The hot-rolled steel sheet is cold-rolled to obtain a cold-rolled steel sheet. The cold-rolled steel sheet is heated at a heating temperature T1 of 750 to 950° C. for 10 to 500 seconds, cooled to a cooling stop temperature T2 of 120° C. or higher and lower than 280° C., and then heated to a reheating temperature T3 of 280 to 400° C., and then recooled without being held at the reheating temperature T3. The heat impact index P from the reheating temperature T3 to (T3-30)°C represented by the following formula (1) is 4000 to 6200, P=T3(log(5t)+12) …(1) In the formula (1), t is the cooling time from the reheating temperature T3 to (T3-30)°C, in seconds.
7. The method for producing a high-strength steel sheet according to claim 5 or 6, wherein: The cold-rolled steel sheet is subjected to a plating treatment.
8. The method for producing a high-strength steel sheet according to claim 7, wherein: The plating treatment is hot-dip galvanizing, alloyed hot-dip galvanizing or electro-galvanizing. 9 . A member formed using the high-strength steel sheet according to claim 1 .
10. A method for manufacturing a component, wherein: A member is obtained by subjecting the high-strength steel sheet according to any one of claims 1 to 4 to at least one of a forming process and a joining process.
Citation Information
Patent Citations
High strength steel sheet and manufacturing method therefor
JP2017214647A
High strength steel sheet and manufacturing method therefor
JP2018021231A
High strength steel sheet and manufacturing method therefor
JP2018021233A